1988
DOI: 10.2527/jas1988.66123185x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Shortened Estrous Cycles after Abortion in Beef Heifers

Abstract: Forty-six crossbred Hereford heifers were allotted into five experimental groups. Fenprotalene, a prostaglandin analogue, was administered to induce abortion and (or) to regress the corpus luteum (CL) in four groups of heifers about 75 d after conception. The four groups were 1) pregnant heifers, 2) pregnant heifers with the ovary contralateral to the gravid uterine horn removed 24 h after fenprostalene injection, 3) same as Group 2 but with the ipsilateral, rather than the contralateral, ovary removed and 4) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Preceding estrous cycles of normal length, the first postpartum estrus is frequently associated with a cycle of short duration, generally 8 to 10 d in length, with P 4 ≥ 1 ng/mL (Odde et al, 1980;Peters and Lamming, 1984;Wright et al, 1988). An improperly steroid-conditioned uterus is thought to be the cause of premature release of PGF 2α and an early demise of the corpus luteum.…”
Section: Discussionmentioning
confidence: 99%
“…Preceding estrous cycles of normal length, the first postpartum estrus is frequently associated with a cycle of short duration, generally 8 to 10 d in length, with P 4 ≥ 1 ng/mL (Odde et al, 1980;Peters and Lamming, 1984;Wright et al, 1988). An improperly steroid-conditioned uterus is thought to be the cause of premature release of PGF 2α and an early demise of the corpus luteum.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that patterns of follicular than preceding so. (Kesler et al, 1985;Copelin et al, 1987;Wright et al, 1988). Whether the mechanism causing premature luteal regression after FO is triggered by a preovulatory follicular determinant is unknown.…”
Section: Sdmentioning
confidence: 99%